Clinical guidelines for total temporomandibular joint replacement. Issue 1 (November 2020) - Yoda, Tetsuya; Ogi, Nobumi; Yoshitake, Hiroyuki; Kawakami, Tetsuji; Takagi, Ritsuo; Murakami, Kenichiro; Yuasa, Hidemichi; Kondoh, Toshirou; Tei, Kanchu; Kurita, Kenichi
Summary: Total joint replacement (TJR) of the temporomandibular joint (TMJ) is a promising surgical procedure and device for treating end-stage diseases of the TMJ. For the functional and aesthetic reconstruction of the oral and maxillofacial head and neck region, TMJ TJR significantly helps maintain the patient's quality of life in terms of a better diet, mastication, speech and social interaction. TMJ TJR was approved by regulatory authorities in 2019 in Japan, thus enabling the clinical application of the TJR system. However, the surgery demands particularly difficult and high-risk procedures, necessitating the prudent selection of indicated patients. The joint committee of the Japanese Society of Oral and Maxillofacial Surgeons and Japanese Society for Temporomandibular Joint is working together to develop an appropriate clinical guideline for TMJ TJR.